The Necessity and Importance of Research and Its Role in Afghan Society - Fayaz Gul Mazloum Yar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research examines the critical role of scientific research in Afghan society, highlighting its necessity for economic, social, and cultural development amid ongoing challenges such as war, poverty, and political instability. Utilizing a qualitative methodology, the study conducts semi-structured interviews with researchers, university professors, and policymakers to gather in-depth insights. Key findings reveal that scientific research significantly contributes to economic development by enhancing education quality, improving infrastructure, and fostering innovation. However, the study identifies substantial barriers to research advancement, including institutional, cultural, and financial constraints. The implications of these findings underscore the urgent need for increased investment in research infrastructure and support mechanisms to facilitate sustainable development and improve the quality of life in Afghanistan. By prioritizing research, the country can leverage knowledge to address its pressing challenges effectively.